Spirituality And Subjective Well Being in Tahfidz Students in Islamic Boarding School - Muhimmatul Hasanah; Abd. Haris (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Tahfidz students have a duty in addition to memorizing the Qur'an as well as students with all their learning tasks. Sometimes this situation makes students depressed which results in stress and depression. The emergence of stress and depression in students can result in low subjective wellbeing so that it can affect performance in memorizing the Qur'an. Spirituality can affect the subjective wellbeing level of tahfidz students, because with spirituality individuals can feel the presence of God and get social support during difficult times. The purpose of this study was to determine the effect of spirituality on subjective wellbeing in tahfidz students at Islamic boarding schools. The hypothesis proposed is that there is an influence of spirituality on the subjective wellbeing of tahfidz students in Islamic boarding schools. The subjects in this study amounted to 92 tahfidz students at the Sunan Drajat Islamic Boarding School Lamongan. Taking the subject using purposive sampling technique. Data collection techniques used measuring tools for spirituality level and measuring tools for subjective well-being which were arranged using a modified Likert scale model. The analytical technique used to analyze the data in this study is simple linear regression. The results showed that the R value or coefficient of determination was 0.889, which means that there is a very strong relationship between spirituality and subjective wellbeing. R square value of 0.813 indicates the influence of the independent variable (spirituality) on the dependent variable (subjective wellbeing) of 81.3%.